(untitled) (BIRDEM Medical Journal, 2025)
Background: In developing countries like Bangladesh, etiologies of acute febrile illness (AFI) remain largely unknown due to limited diagnostic facilities. AFI is often associated with high morbidity and mortality, due to high prevalence of local individual diseases. The prioritization of the differential diagnosis of a clinical syndrome of AFI is needed. Aim of this study was to evaluate the etiology and clinical spectrum of AFI of the patients attending a tertiary level hospital in Dhaka. Methods: This cross-sectional study was carried out in the Department of Internal Medicine of BIRDEM General Hospital, Dhaka during the period of July 2019 to June 2020. Patients with AFI, defined as fever for less than 2 weeks duration, were approached for this study. In this study all the diagnosed cases of AFI were taken, to evaluate their etiology, clinical and laboratory parameters. Informed written consent were obtained. Data were collected by convenient sampling in a preformed structured data sheet containing history, clinical finding, laboratory investigation and imaging studies. Collected data were analyzed using the statistical software SPSS 22. Results: Total patients were 344, mean age of the study participants was 43.47 (±14.78) (range 19 to 63) years with a majority in age group 51-60 years (25.30%). Female predominance was observed (58%). Fever pattern was intermittent in 52% patients and continued in 48% patients. Presenting clinical features were body ache, abdominal pain, rash, arthralgia, vomiting, cough, respiratory distress, tachypnea, chest pain, diarrhea, weakness, headache and myalgia. Frequency of clinical features varied with diagnosis. Urinary tract infection (UTI) was the commonest (37.80%) etiology followed by dengue (33.70%), pneumonia (10.50%), typhoid (9%), typhus (5.20%), acute gastroenteritis (2.90%) and leptospirosis (0.90%). The co-morbidities among patients were diabetes mellitus (39.50%), hypertension (27.90%), ischemic heart disease (4.65%) and chronic kidney disease (2.90%). Conclusion: In this study UTI was the commonest etiology of AFI followed by dengue, pneumonia, typhoid, typhus, acute gastroenteritis and leptospirosis. BIRDEM Med J 2025; 15(2): 58-62